Forgotten and Invisible Labourers: Domestic Workers in Singapore and Taiwan - Ng, Lynn (Serikat Pengajar Hak Asasi Manusia Indonesia, 2022)
This paper is about legal yet unjust systems of domestic servitude; the oppressive circumstances that ‘foreign maids’ the world over face as unappreciated, unrecognised, and undervalued workers in the invisible domestic space. Regardless of political culture and regime - liberal democracies to authoritarian governance – ‘maids’ are excluded from normal labour standards. The author explains and discusses the legal blind spots, loopholes, and oversight of labour clauses for foreign domestic workers (FDWs) in the East Asian states of Singapore and Taiwan. This paper aims to spark critical conversations about the public/private divide, also the feasibility of enacting home-based legislation for private household workers. It uses the reviewed literature – relevant research studies, government websites, and news sources – and interview findings to advance its main claims. Between May 2021 and July 2022, the author conducted online semi-structured interviews on WhatsApp/Zoom with 61 people who were directly or indirectly involved in eldercare provision: FDWs, domestic employers, recruitment agency managers, unpaid family caregivers, and NGO workers. The author’s analysis shows that FDWs, called ‘maids’ in the local parlance, face a myriad of shocking abuses by sending/receiving governments, unscrupulous recruitment agencies, and host employers who view them as private property (owned) rather than human beings with needs. This paper argues that FDWs deserve to be respected and included in formal labour laws like the rest of the workforce, to better safeguard their physical safety, mental wellbeing, and personal dignity. In doing so, the paper contributes to the growing literature on migrant domestic labour by foregrounding the legal architectures of exclusion and offering a comparative, empirically grounded critique of how East Asian states perpetuate structural inequalities through regulatory neglect.